HASIL BELAJAR KOGNITIF FISIKA SISWA MELALUI PENERAPAN PENDEKATAN INKUIRI PADA MATERI TERMODINAMIKA KELAS XI MIA MAN 2 PEKANBARU BERBASIS KURIKULUM 2013 - Witari Amelia; Zulhelmi Zulhelmi; Fakhruddin Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was aimed to determine students’ physics learning result by applying inquiry approach. This research was conducted at MAN 2 Pekanbaru from February to May 2018. Two groups of samples were choose from homogeneous classes. Quasi experiments in the form of intact group comparison was used in this study. The data was obatained from students’ physics learning result test which consisted of 20 items of multiple choice. Descriptive and inferential analysis were used for data analysis. Based on descriptive analysis, the average of students’ absorption ability in the experimental class was 84,21% and 78,05% for control class, this indicated that the effectiveness of student learning in experiment class was higher than in the control class. Based on inferential analysis through independent sample t test sig value. (2-tailed) = 0.032 < 0.05 was obatained. This mean that there was a significant difference in students’ physics learning result. It can be concluded that the application of inquiry approach could enchace students’ physics study result on thermodynamic material at XI MIA class MAN 2 Pekanbaru.Keywords: Students Physics Study Result, Inquiry Approach, Thermodynamic